Antecedents and Extent of Financial Inclusion : A Cross-Sectional Study - Tandon, Priyanka; Singh, Anurag Bhadur (Indian Journal of Finance, 2021)
According to the latest study by World Bank on financial inclusion, globally 31% of people are excluded from access to formal financial services. But despite growth in account ownership, inequality persists. The objective of the present study was to examine the current status of financial inclusion and to further explore the factors leading towards the lower level of financial access among the households. The study was conducted in four districts of the National Capital Region in India namely, Ghaziabad, Noida, Gurugram, and Faridabad, with a sample size of 300 respondents between the period of 2018 – 2019. The study is unique in nature, as the survey was conducted both in rural and urban areas. The factor analysis technique was applied to explore a large set of variables into few factors affecting the financial inclusion. Further, the households were grouped into three degrees on the basis of their financial behavior and attitude. Finally, the study concluded that supply-side and demand-side factors were the main factors for the lower access to basic banking services. Furthermore, financial attitude, financial knowledge, and financial behavior were the factors shaping the minds of the respondents. The results revealed that majority of the respondents fell under Degree 1, that is, having access to banking products, but their level of financial literacy and active usage of bank accounts was significantly low. Therefore, it is concluded that though a sufficient number of people had a formal bank account, there existed a low level of financial literacy due to which they were not active users of financial services.